Thord Ehnevid: Forsamlingsetik - Lindhardt, Poul Georg (Grundtvig-studier, 1971)
Thord Ehnevid, Församlingsetik. Studier över Grundtvig, Morten Pontoppidan och Einar Billing Reviewed by P. G. Lindhardt This thesis for the doctorate has arisen out of a concrete historical situation, viz. the establishment of large municipal units in Sweden, few years before the corresponding Danish reform in 1970. These reforms have given rise to the question: is the geographically limited parish nothing but a product of human reason that may be disintegrated without any harm, or are inalienable religious and cultural values inherent in it?— Whether this alternative is regarded as genuine or not, the reforms referred to do present problems to our view of the church, congregation, parish, etc. The thesis attempts to illuminate these problems by seeing them in the light of the opinions of three prominent personalities on the process of disintegration that affected the traditional Scandinavian state church system in the 19th and early 20th centuries.Ehnevid is aware of the psychological peculiarities of the three men, and of the fact that the differences between them are linked with different positions and different polemical situations; but historical coincidences of that kind are greatly reduced by the systematic character of the work. The price that is paid for the systematic clarity is a certain inclination to abstractions, and a strong tendency towards schematism. Ehnevid began his work as a Pontoppidan study, and this section forms the largest and most thorough-going part of the thesis. But the two other studies are extremely valuable too. The reviewer, however, has never referred to Billing’s view of the church as ‘statistic’, only ‘static’.